2015
DOI: 10.3389/fpsyg.2015.00823
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of speaker’s referential expressions to an addressee’s likely knowledge and link with theory of mind abilities

Abstract: To communicate cooperatively, speakers must determine what constitutes the common ground with their addressee and adapt their referential choices accordingly. Assessing another person’s knowledge requires a social cognition ability termed theory of mind (ToM). This study relies on a novel referential communication task requiring probabilistic inferences of the knowledge already held by an addressee prior to the study. Forty participants were asked to present 10 movie characters and the addressee, who had the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
1
21
0
1
Order By: Relevance
“…Although many researchers have proposed a theoretical link between children's mentalizing abilities and communicative perspective taking (Achim, Fossard, Couture & Achim, 2015; Nilsen & Fecica, 2011; Sperber & Wilson, 2002), only a handful of studies have directly examined the relation between these two capacities. This research has shown that three- to six-year-old children's accurate production and repair of referential statements is positively related to their performance on both visual perspective-taking tasks (Roberts & Patterson, 1983) as well as standard measures of false-belief understanding (Resches & Pereira, 2007).…”
Section: Cognitive Abilities and The Integration Of Perspective And Linguistic Informationmentioning
confidence: 99%
“…Although many researchers have proposed a theoretical link between children's mentalizing abilities and communicative perspective taking (Achim, Fossard, Couture & Achim, 2015; Nilsen & Fecica, 2011; Sperber & Wilson, 2002), only a handful of studies have directly examined the relation between these two capacities. This research has shown that three- to six-year-old children's accurate production and repair of referential statements is positively related to their performance on both visual perspective-taking tasks (Roberts & Patterson, 1983) as well as standard measures of false-belief understanding (Resches & Pereira, 2007).…”
Section: Cognitive Abilities and The Integration Of Perspective And Linguistic Informationmentioning
confidence: 99%
“…However, including more information in a description than strictly necessary does not jeopardize communication (in this case, referent identification for the addressee). It would rather be to provide too little information—being referentially under-specific—that may be seen as reflecting an egocentric tendency, detrimental for communication (see also Achim et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…People with FBU will be able to represent that when the boy comes back and looks for the chocolate, he will act on his false belief to look for the chocolate in the blue cupboard. FBU has been associated with a wide range of social and cognitive outcomes (Farrar et al, 2017b), including communication skills (Achim et al, 2015), peer popularity (Slaughter et al, 2015), and academic achievement (Blair & Razza, 2007). Deficits in FBU contribute to social impairments in autism spectrum disorders (Baron-Cohen et al, 1985), frontal variant frontotemporal dementia (fvFTD; Gregory et al, 2002), and substance use disorder (Sanvicente-Vieira et al, 2017), etc.…”
mentioning
confidence: 99%